Totally extra-peritoneal repair for acute incarcerated femoral hernia with intestinal obstruction. (2017) - Kim, Guowei; Yan So, Jimmy Bok; Shabbir, Asim
Highlights: Discussion on minimally invasive approaches to acute groin hernia surgery. Technical 'tips and tricks' for emergency laparoscopic repair of femoral hernia. Review of the current literature. Abstract: Introduction: Femoral hernias frequently present with incarceration, resulting in obstruction and strangulation. Laparoscopic groin hernia repairs have been shown in the elective setting to be an effective alternative to open repair. Acute incarceration of groin hernia with obstruction, though previously seen as a relative contraindication, has been increasingly repaired with minimally invasive techniques, with the potential benefit of avoiding the morbidity associated with a laparotomy. Presentation of case and discussion: We describe a case of an acutely incarcerated femoral hernia with intestinal obstruction that was repaired using the totally extra-peritoneal approach. A releasing incision was performed to facilitate reduction of hernia prior to mesh repair. Diagnostic laparoscopy through a separate incision was then performed. Conclusion: This modification of the TEP repair technique for the acutely incarcerated and obstructed femoral hernia serves to minimise potential contamination by keeping the pre-peritoneal plane strictly separate from the intra-peritoneal space.